Описание личинки поденки Rhithrogena bajhuvae Sоwa (Ephemeroptera, Heptagehiidae) из бассейна Амура - Байкова, О.Я. (Вестник зоологии, 1977)
A new species R. bajkovae Sowa (Sowa, 1973) from the Amur basin was described at the adult stage by doctor R. Sawa. A larva of this species was obtained by the author. The paper describes for the time the unknown larva of the R. bajkovae species determined previously by the wing phase. The identification key is presented for species close according to the imago and larvae.